2020
DOI: 10.3390/met10020202
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Shielding Interactions between Double Cracks on Crack Growth Behaviors under Fatigue Loading

Abstract: In this paper, the interactions between double cracks with a co-bisector-line were investigated theoretically and experimentally. Fatigue crack growth tests of specimens with a single crack or double cracks were carried out to measure the crack growth rates, and finite element calculations were performed to obtain the stress intensity factors at crack tips. It was found that when the double cracks are in co-bisector-line, they present shielding interactions which reduce the stress intensity factors at crack ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…It should be noted that this shielding effect was found to be in an inverse relationship with the horizontal separation distance, as the separation distance increases the interaction impact is reduced. This interaction influence for double parallel cracks found to be similar to that of parallel cracks found in plates (Han, Qian, and Li 2020) and in solid cylinders (Awang et al 2017), where both studies explored the interaction influence of parallel cracks. However, in order to quantify this rate of interaction between the cracks, the interaction factor (Ѱ) is determined for this purpose in the next section.…”
Section: Sifs Distributionsupporting
confidence: 67%
“…It should be noted that this shielding effect was found to be in an inverse relationship with the horizontal separation distance, as the separation distance increases the interaction impact is reduced. This interaction influence for double parallel cracks found to be similar to that of parallel cracks found in plates (Han, Qian, and Li 2020) and in solid cylinders (Awang et al 2017), where both studies explored the interaction influence of parallel cracks. However, in order to quantify this rate of interaction between the cracks, the interaction factor (Ѱ) is determined for this purpose in the next section.…”
Section: Sifs Distributionsupporting
confidence: 67%
“…In addition, Han et al found that when double cracks are located on the bisector, shielding interaction will occur, which will reduce the stress intensity factor and crack growth rate at the crack tip. 70 However, thus far, there are still disputes about the physical mechanism of the formation of repulsion regions in EP cracks.…”
Section: Crack Patterns By In-plane Stressmentioning
confidence: 99%
“…However, numerical methods have proven to be a practical approach to solving this problem. Another vital issue for multiple edge crack problems is the interaction between the cracks [26][27][28][29]. Han et al [30] investigated experimentally and numerically the interaction between two parallel cracks.…”
Section: Introductionmentioning
confidence: 99%